1998
DOI: 10.1073/pnas.95.5.1996
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci and metabolic pathways

Abstract: The interpretation of quantitative trait locus (QTL) studies is limited by the lack of information on metabolic pathways leading to most economic traits. Inferences about the roles of the underlying genes with a pathway or the nature of their interaction with other loci are generally not possible. An exception is resistance to the corn earworm Helicoverpa zea (Boddie) in maize (Zea mays L.) because of maysin, a C-glycosyl f lavone synthesized in silks via a branch of the well characterized f lavonoid pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 23 publications
2
70
0
Order By: Relevance
“…In maize, the only case to date where the complete set of genes from a pathway has been examined, the maysin content of corn silks was associated with alleles of both regulatory and structural loci (1)(2)(3)(4). Other results from both maize (5,6) and Arabidopsis thaliana (7) have shown that variability in quantitative measurements of overall enzymatic activity can be attributed to structural loci or closely linked elements.…”
mentioning
confidence: 89%
“…In maize, the only case to date where the complete set of genes from a pathway has been examined, the maysin content of corn silks was associated with alleles of both regulatory and structural loci (1)(2)(3)(4). Other results from both maize (5,6) and Arabidopsis thaliana (7) have shown that variability in quantitative measurements of overall enzymatic activity can be attributed to structural loci or closely linked elements.…”
mentioning
confidence: 89%
“…Several QTLs for glycolytic enzyme levels and glucosinolate production in Arabidopsis map to the locations of genes that encode the responsible enzymes (Mitchell-Olds and Pedersen 1998;Kliebenstein et al 2001). In maize, QTLs for concentration of maysin, an important contributor to earworm resistance, have been mapped in several crosses (McMullen et al 1998 Note. Genes that have been identified as flowering time genes on the basis of mutant analysis are described as functional candidates, regardless of whether a candidate gene approach was used to isolate the trait locus.…”
Section: Finding the Genesmentioning
confidence: 99%
“…The region in the vicinity of p1 has been identified as a major QTL for the control of levels of silk maysin, a C-glycosyl flavone that deters feeding by corn earworm (Byrne et al 1996;Lee et al 1998;McMullen et al 1998). Maysin accumulation is correlated with a phenotype termed silk browning, in which the cut ends of silks turn brown due to the oxidation of flavones (Byrne et al 1996;Lee et al 1998;McMullen et al 1998;Guo et al 2001;Rector et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Maysin accumulation is correlated with a phenotype termed silk browning, in which the cut ends of silks turn brown due to the oxidation of flavones (Byrne et al 1996;Lee et al 1998;McMullen et al 1998;Guo et al 2001;Rector et al 2003). Both p1 and p2 genes are expressed in maize silk (Zhang et al 2000), and both encode highly similar R2R3-Myb proteins with a similar potential to activate flavonoid biosynthesis in transgenic cell lines (P. .…”
Section: Resultsmentioning
confidence: 99%